EVALAUTION MODEL OF THE FUNCTIONAL CONDITION OF THE RADAR STATIONS ATC, CONSIDERING EXTERNAL CHANGES - V. E. Emelyanov (Научный вестник МГТУ ГА, 2016)
The article deals with specification evaluation model of radars reliability which operate in different working conditions, resulting from exposure to various external disturbances. The assessment possibility of the operating expenses level according to the value which depends on the emission efficiency of the signal which is determined by external influences is also shown.